2018
DOI: 10.2147/oajsm.s146716
|View full text |Cite
|
Sign up to set email alerts
|

Management of injuries in snowboarders: rehabilitation and return to activity

Abstract: Snowboarding has seen a continuous increase in popularity, leading to an increase in the number of snowboarding injuries seen in orthopedic practice. Upper-extremity injuries are more common than lower-extremity, spine, and pelvis injuries. In this review, we focus on the most common snowboarding injuries of the extremities, spine, and pelvis and provide an overview of their respective rehabilitation and return-to-sport protocols. Despite many of the injuries seen in snowboarding also occurring in other sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(145 reference statements)
1
3
0
Order By: Relevance
“…Our study found that clavicle fractures in skiers made up 2.8% of total injuries as compared with prior findings of 2.2%, 1 while clavicle fractures in snowboarders were 3.4% of total injuries compared with 0.8% to 5% noted in other studies. 1,8,14,31 Consistent with prior clavicle fracture data, we found that the midclavicle was the most commonly fractured portion of the bone. 3,5,6,13,18,25 In our study, midclavicle fractures accounted for approximately 85% of all clavicle fractures.…”
Section: Figuresupporting
confidence: 84%
See 2 more Smart Citations
“…Our study found that clavicle fractures in skiers made up 2.8% of total injuries as compared with prior findings of 2.2%, 1 while clavicle fractures in snowboarders were 3.4% of total injuries compared with 0.8% to 5% noted in other studies. 1,8,14,31 Consistent with prior clavicle fracture data, we found that the midclavicle was the most commonly fractured portion of the bone. 3,5,6,13,18,25 In our study, midclavicle fractures accounted for approximately 85% of all clavicle fractures.…”
Section: Figuresupporting
confidence: 84%
“…Our study found that clavicle fractures in skiers made up 2.8% of total injuries as compared with prior findings of 2.2%, 1 while clavicle fractures in snowboarders were 3.4% of total injuries compared with 0.8% to 5% noted in other studies. 1,8,14,31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper extremity is injured nearly twice as often in snowboarding than skiing, with approximately 50% of injuries involving this region, and fractures occur more than twice as often as in alpine skiers (Kim, Endres, Johnson, Ettlinger, & Shealy, 2012;Mirhadi, Ashwood, & Karagkevrekis, 2015). Wrist injuries, particularly fractures, are the most common snowboarding injuries, while knee injuries are usually less severe, with one study reporting a complete ligament rupture in only 2 of 62 reported knee injuries (Helmig, Treme, & Richter, 2018). Beginners are at an increased risk of wrist injuries, mostly due to frequent falls, and experts tend to have more ankle injuries, often associated with freestyle maneuvers, and requiring medical attention (Ogawa, Sumi, H., Sumi, Y., & Shimizu, 2010).…”
Section: Introductionmentioning
confidence: 99%